Eviction of unlawful occupiers of property in Malaysia- judicial responses and policy - Syed Abdul Kader, Sharifah Zubaidah; Ali, Zuraidah; Mohamad, Nor Asiah (LexisNexis, 2013)
Eviction is the act of recovering possession of property that is precieved to be under the unlawful possession of another.This article focus largely on the land and planning law aspects, the remedy under specific relief and the rules of courts as well as reference to humanitarian law when suggesting law reform.